MicroRNAs as Biomarkers for Predicting Complications following Aneurysmal Subarachnoid Hemorrhage - Wang, Wang-Xia; Springer, Joe E.; Hatton, Kevin W. (International journal of molecular sciences, 2021)
Aneurysmal subarachnoid hemorrhage (aSAH) is a high mortality hemorrhagic stroke that affects nearly 30,000 patients annually in the United States. Approximately 30% of aSAH patients die during initial hospitalization and those who survive often carry poor prognosis with one in five having permanent physical and/or cognitive disabilities. The poor outcome of aSAH can be the result of the initial catastrophic event or due to the many acute or delayed neurological complications, such as cerebral ischemia, hydrocephalus, and re-bleeding. Unfortunately, no effective biomarker exists to predict or diagnose these complications at a clinically relevant time point when neurologic injury can be effectively treated and managed. Recently, a number of studies have demonstrated that microRNAs (miRNAs) in extracellular biofluids are highly associated with aSAH and complications. Here we provide an overview of the current research on relevant human studies examining the correlation between miRNAs and aSAH complications and discuss the potential application of using miRNAs as biomarkers in aSAH management.